2006
DOI: 10.1194/jlr.r600008-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Thematic review series: Patient-Oriented Research. What have we learned about HDL metabolism from kinetics studies in humans?

Abstract: Plasma measurements of lipids, lipoproteins, and apolipoproteins provide information on the static levels of these fractions without providing key information on the dynamic fluxes of lipoproteins in the circulation. Kinetics studies, in contrast, provide additional information on the production and clearance rates of lipoproteins and the flow of lipids and apolipoproteins through lipoprotein fractions. This information is crucial in accurately delineating the metabolism of HDL in plasma, because plasma concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 91 publications
1
20
0
Order By: Relevance
“…Therefore, cellulose treatment might not be able to reverse the trend of exacerbated insulin resistance without diet restriction or other treatment. According to a previous study, patients with insulin resistance exhibit increased HDL catabolism, which might explain the abnormal trend in HDL levels we observed in the cellulose group [32]. The influence of cellulose on sugar metabolism warrants further exploration.…”
Section: Discussionmentioning
confidence: 74%
“…Therefore, cellulose treatment might not be able to reverse the trend of exacerbated insulin resistance without diet restriction or other treatment. According to a previous study, patients with insulin resistance exhibit increased HDL catabolism, which might explain the abnormal trend in HDL levels we observed in the cellulose group [32]. The influence of cellulose on sugar metabolism warrants further exploration.…”
Section: Discussionmentioning
confidence: 74%
“…In the insulinresistant diabetic state, CETP and hormone-sensitive lipase modify HDL composition to triglyceride-rich HDL and then ApoA-I dissociates from HDL [48]. Released apoA-I can be filtered by the renal glomerulus and then degraded by proximal renal tubular cells [49]. However, if the HDL particle releases ApoA-I in patients with diabetes, Efflux-hdl in this study was underestimated, because applied HDL (which was adjusted for 5 mg/mL ApoA-I) would contain a greater number of HDL molecules in the fraction.…”
Section: Discussionmentioning
confidence: 98%
“…Beyond its putative role of sequestering and transporting cholesterol and other detrimental products back to the liver for disposal, HDL is believed to inhibit endothelial inflammation and promote production of endothelial nitric oxide (NO) and prostacyclins [39]. Variation in HDL levels is believed to be primarily associated with variation in clearance, except in dietary studies which have identified that fat intake affects HDL production or transport rates [61]. Although we cannot identify the specific metabolic effects on HDL-C variation here, as plasma levels of APOA-1 are not associated with carbohydrate intake, our findings suggest that catabolism may be the more likely mechanism affecting HDL-C variation in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Kataoka et al [32] study examining the relationship of APOE polymorphisms to plasma lipids in the original Strong Heart Study individuals (n = 4,410), reported sexspecific variation associated with APOE polymorphisms. Genotype was not significantly associated with HDL-C variation in males (ages [45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64], however, in females, a significant trend for HDL-C levels was noted in all female subgroups studied: normal and diabetic, premenopausal and menopausal. HDL-C was higher in females carrying an e2 and lower in individuals carrying an e4 than for females with e3/3 genotypes.…”
Section: Genotype Effectsmentioning
confidence: 99%